Optimization of Mango Flour Formulation (Mangifera indica L) Arumanis Variety using Response Surface Methodology - Silvia Oktavia Nur Yudiastuti; Titik Budiati; Yossi Wibisono; Oryza Ardhiarisca; Findi Citra Kusumasari; Wiwik Handayani; Yesi Indah Dwi Kusuma Hariyanti (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2024)
Mango (Mangifera indica L) is one of commodities with high food loss rate due to the characteristics of mango, which is easily spoiled and difficult to store. One of the strategies to reduce mango food loss caused by post-harvest handling is the diversification of mango products. Mango flour can be developed to minimize mango food waste and enhance its added value. This study aimed to determine the optimum formulation for making mango flour. The study used Response Surface Methodology (RSM) type Central Composite Design (CCD) to optimize mango flour yield, using three factors: rice flour concentration (X1: 2 5%), maltodextrin concentration (X2: 2-5%), and tapioca flour concentration (X3: 2-5%). The significance of response was carried out using analysis of variance (ANOVA) at the 95% confidence level (p<0.05). The linear model was the model suggested by software. Model analysis showed that rice flour and tapioca flour concentration significantly affected mango flour yield, while maltodextrin did not have a considerable impact. Based on the results of this study, the optimum conditions in making mango flour were found using rice flour concentration of 4.94%, maltodextrin concentration of 2.25%, and tapioca flour concentration of 4.88% to produce mango flour yield of 20.9578%. Keywords: Mango flour, Optimization, Response surface methodology, Yield.